2018
DOI: 10.1007/s13593-018-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

The physiological responses of cacao to the environment and the implications for climate change resilience. A review

Abstract: Cacao (Theobroma cacao L.) is a tropical perennial crop which is of great economic importance to the confectionary industry and to the economies of many countries of the humid tropics where it is grown. Some recent studies have suggested that climate change could severely impact cacao production in West Africa. It is essential to incorporate our understanding of the physiology and genetic variation within cacao germplasm when discussing the implications of climate change on cacao productivity and developing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
125
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 129 publications
(186 reference statements)
2
125
0
8
Order By: Relevance
“…Yet, further work is needed to better characterize the sensitivity to drought across populations and among individuals within populations in T. cacao . Although it is generally found that T. cacao is sensitive to drought (Lahive et al, 2019), there is limited information about the variability in drought susceptibility across populations (Atayese et al, 2012), making it difficult to further characterize how these SNPs contribute to drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, further work is needed to better characterize the sensitivity to drought across populations and among individuals within populations in T. cacao . Although it is generally found that T. cacao is sensitive to drought (Lahive et al, 2019), there is limited information about the variability in drought susceptibility across populations (Atayese et al, 2012), making it difficult to further characterize how these SNPs contribute to drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the drought disadvantage of cocoa agroforestry was perceived by a limited proportion of household heads, it is somehow supported by more recent studies [7,43,49]. For instance, Abdulai et al [43] found in the FSTZ of Ghana that cocoa plants under Albizia ferruginea and Antiaris toxicaria suffered 100% and 77% mortality respectively during the 2015/16 drought, while cocoa in full sun, suffered only 12% mortality [50].…”
Section: Discussionmentioning
confidence: 99%
“…Agroforestry (the integration of shade trees) has received considerable attention in the literature as an effective climate-resilient strategy in cocoa production [7,8,9]. Nevertheless, cocoa agroforestry adoption is low [10,8] as farmers increasingly switch to full-sun monoculture [10,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The extreme changes might shape crops and ultimately the yield of cocoa. In a very interesting review, Lahive et al [ 145 ] considered the current research on cocoa’s physiological responses to CC. In the present paper, we consider the influence of CC on cocoa mycobiota during the different production steps because it is possible that new interactions of the fungi may affect the cocoa production chain and the final product’s quality ( Figure 3 ).…”
Section: What About Climate Change?mentioning
confidence: 99%